(untitled) (Ustozlar uchun, 2024)
Abstract: The article talks about the importance of using new pedagogical technologies in the teaching of English, and analyzes all the possibilities of the student, taking into account the complexity of mastering the subject. Also, examples of new methods in language development are given and its importance is revealed.